Influence of Chemical Treatment on the Physico-mechanical Characteristics of Natural Fibers Extracted from the Barks of Vachellia Farnesiana - Vijay Raghunathan; Jafrey Daniel James Dhilip; Gowtham Subramanian; Harikrishnan Narasimhan; Chandru Baskar; Amarnath Murugesan; Anish Khan; Ahmed Al Otaibi (Journal of Natural Fibers, 2022)
In recent decades, the production of natural fiber composites has increased due to their biodegradability and lower costs. In the current work, Vachellia farnesiana fibers were selected and extracted by the manual retting process. The obtained Vachellia farnesiana fibers were chemically treated with hydrochloric acid (HCl) and sodium hydroxide (NaOH) solutions. The chemically treated and untreated Vachellia farnesiana fibers were characterized for physical, chemical, tensile, morphological, and thermal properties. Test results showed that the cellulose content was 47.8 ± 0.697 weight % for NaOH treated Vachellia farnesiana fibers with reduced moisture and amorphous contents. HCl treated Vachellia farnesiana fiber showed more cellulose content removal, which resulted in degradation of its properties due to the acidic nature of HCl.